PENGARUH TRUST, PRICE DAN SERVICE QUALITY TERHADAP INTENTION TO PURCHASE PELANGGAN BHINNEKA.COM - Nurcahyo, Rianto; Andry, Dennis; Kevin, Kevin (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The purpose of this study is to identify and understand the factors that can influence the intention to purchase through trust, price, and service quality on consumers Bhinneka.com. This research uses quantitative approach by distributing questionnaires to 100 respondents Bhinneka.com. Data analysis method used in this research is simple and multiple regression analysis. The result shows that the three variables used have a positive influence on intention to purchase variable. The most dominant variables in explaining the variation of intention to purchase are service quality variable of 35.5%, the price of 17.2%, and trust of 24.6%. Keywords: service quality, price, trust, intention to purchase